Examining Incarcerated Students’ Educational Realities in Prison - Vimbi Petrus Mahlangu (Iranian Journal of Educational Research)
Objective: This study examines the experiences of 12 incarcerated students in a Namibian jail who were working towards obtaining formal qualifications. The objective was to examine and evaluate the specific challenges, opportunities, and experiences faced by incarcerated individuals who are pursuing education while in prison. The participants were deliberately chosen based on the premise that they were actively involved in formal education. Methods: The data collection strategy utilized literature review and tape-recorded interviews enabling the students to articulate their own experiences and difficulties in managing the dual demands of education and prison life. Data analysis: An English-speaking transcriber transcribed the recorded interviews verbatim to guarantee precision. The transcriptions were subsequently examined using an interpretive framework, allowing the researcher to gain a profound comprehension of the subtle and intricate experiences of the individuals. This technique yielded valuable insights into the strategies employed by these individuals to negotiate the intricate process of pursuing scholastic objectives within the confining and frequently difficult prison setting. Results: Prison students face a lack of independence, disturbances from fellow convicts, and limited resources that pose challenges to their educational endeavors. Despite these obstacles, several individuals have exceptional intellectual abilities and benefit from the organized system and educational opportunities provided in prison. Nevertheless, the presence of excessively populated classrooms, obsolete learning resources, and limited time availability further exacerbate their academic endeavors. Conclusions: Individuals who are currently in prison view education to achieve personal development, acquire new skills, and enhance their chances of finding job after their release